2010
DOI: 10.1177/172460081002500101
|View full text |Cite
|
Sign up to set email alerts
|

Can the Acute-Phase Reactant Proteins be Used as Cancer Biomarkers?

Abstract: The association between the acute-phase reactant proteins (APRPs) and cancer has long been established. There have been numerous reports correlating altered levels of various APRPs with different types of cancers. However, researchers are often quick to dismiss the use of these APRPs as potential biomarkers for the diagnosis and monitoring of cancer because alterations in APRP concentrations are observed in a wide range of diseases. Recent progress in proteomics studies which profiled the serum proteins of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 78 publications
2
39
0
Order By: Relevance
“…It had been established that APRPs and cancer abscessions are linked, and recent discoveries through proteomic technologies have shown that different types of cancers have different APRP alterations [96]. Haptoglobin (Hp) is one such example of an acute phase tetrameric (α2β2) glycoprotein whose increased levels have been reported in breast cancer [97], ovarian cancer [98] and pancreatic cancer [99].…”
Section: Lung Cancer Protein Biomarkers In Serum: Current Statusmentioning
confidence: 99%
“…It had been established that APRPs and cancer abscessions are linked, and recent discoveries through proteomic technologies have shown that different types of cancers have different APRP alterations [96]. Haptoglobin (Hp) is one such example of an acute phase tetrameric (α2β2) glycoprotein whose increased levels have been reported in breast cancer [97], ovarian cancer [98] and pancreatic cancer [99].…”
Section: Lung Cancer Protein Biomarkers In Serum: Current Statusmentioning
confidence: 99%
“…However, traditionally immunoassays and techniques were replaced by modern proteomic analyses, and despite all the challenges, unique combinations of APRPs were recently described for several cancers 83 . Therefore, MALDI-TOF mass spectrometric analysis identifies serum amyloid A as a valuable prognostic marker for all stages of melanoma, with increased specificity and sensitivity for early stages when combined with C reactive protein.…”
Section: Circulatory Inflammatory Markersmentioning
confidence: 99%
“…Ceruloplasmin blocks the copper ion-activated production of toxic oxygen compounds and protects cells from oxidative stress (26). Ceruloplasmin protein is expressed in pancreatic, nasopharyngeal and germline ovarian cancers (27). Ceruloplasmin promoter activation is specifically and efficiently enhanced in ovarian cancer (28).…”
Section: Discussionmentioning
confidence: 99%